Students' Perceptions on an Interprofessional Ward Round Training – A Qualitative Pilot Study - Nikendei, C. (GMS J Med Educ, 2016)
Introduction: Ward rounds are an essential activity for interprofessional teams in hospital settings and represent complex tasks requiring not only medical knowledge but also communication skills, clinical technical skills, patient management skills and team-work skills. The present study aimed to analyse final year students’, nurses’ as well as physiotherapists’ views on a simulation-based interprofessional ward round training. Methods: In two successive passes a total number of 29 final year students, nursing students and physiotherapy students (16 in the first run, 13 in the second) volunteered to participate in two standardized patient ward round scenarios: (1) patient with myocardial infarction, and (2) patient with poorly controlled diabetes. Views on the interprofessional ward round training were assessed using focus groups. Results: Focus group based feedback contained two main categories (A) ward round training benefits and (B) difficulties. Positive aspects enfolded course preparation, setting of the training, the involvement of the participants during training and the positive learning atmosphere. Difficulties were seen in the flawed atmosphere and realization of ward rounds in the daily clinical setting with respect to inter-professional aspects, and course benefit for the different professional groups. Conclusion: The presented inter-professional ward round training represents a well received and valuable model of interprofessional learning. Further research should assess its effectiveness, processes of interprofessional interplay and transfer into clinical practice.